Experimental Investigation of the Interaction Between Human Serum and Troxerutin by Fluorescence Spectroscopy - Zhang, Jihua; Zhao, Zhimin; Wang, Tianhu (Asian Journal of Chemistry, 2012)
Based on fluorescence spectroscopy technology, the interaction between human serum and troxerutin is investigated. The experimental results showed that only a fluorescence peak at 330 nm arises when the human surem is excited at 250-290 nm. When troxerutin is added, the position of fluorescence peaks has a slight blue shift and its intensity is weakened. It can be obtained that 290 nm is the most suitable excited wavelength for the research of serum-troxerutin's interaction. Moreover, Gaussion fitting curves reveal that the fluorescence of human serum is caused by two fluorophores. The values of I325 and I350 decrease after the addition of troxerutin, which illustrates that both fluorophores can interact with troxerutin.